Global supply chain quality management product recalls and their impact - Flynn, Barbara B.; Zhao, Xiande (Supply chain integration : modeling, optimization, and applications, 2015)
The book presents detailed case studies of six extended global supply chains within three industries: toys, food, and pharmaceuticals. These case studies cover U.S. companies with supply chains that extend into China and provide the perspectives of both U.S. and Chinese executives. It includes coverage of several highly publicized product recalls, including Ford Pinto, Extra Strength Tylenol, melamine-tainted milk, Mattel, and Toyota